Carotid atherosclerosis and cardiovascular health metrics in old subjects from the AGES-Reykjavik study. Issue 1 (September 2015) - Sturlaugsdottir, Ran; Aspelund, Thor; Bjornsdottir, Gudlaug; Sigurdsson, Sigurdur; Eiriksdottir, Gudny; Imai, Cindy Mari; Garcia, Melissa; Launer, Lenore J.; Harris, Tamara B.; Gudnason, Vilmundur
Abstract: Background: Ideal cardiovascular (CV) health by simultaneous presence of 7 ideal health metrics (blood pressure, cholesterol, glucose, smoking, BMI, physical activity and diet) has been defined by the American Heart Association. In the current study we investigated the association of a CV health score (range 0–14), on the extent and progression of carotid atherosclerosis, assessed as carotid intima-media thickness (cIMT) and total plaque area (TPA) by ultrasound at 5 years interval. Methods and results: A total of 219 participants (age 75.6 ± 5.1) from the Age, Gene/Environment Susceptibility (AGES)-Reykjavik study were studied. Men with poor (low) CV health score had greater TPA than those with more optimal (high) score (61.5 (SD: 32.3), 44.4 (24.2) and 37.7 (23.2) mm 2 for those with CV health score ≤6, 7–9 and ≥10 respectively, p < 0.05). In linear analysis for men, log TPA was 0.088 mm 2 (SE: 0.040 p < 0.05) smaller for each additional point in the CV health score. CV health score was not associated with TPA in women, or cIMT in either sex. TPA increased in both sexes between visits. However, CV health score did not predict carotid atherosclerosis progression. Conclusions: CV health score is associated with TPA in older men but not in women. Men with poor CV health score at the baseline visit had more extensive carotid atherosclerosis than those with better CV health score, although it did not predict the progression of carotid atherosclerosis. Highlights: We studied carotid plaque area and cIMT progression in old men and women. We examined cardiovascular health score and carotid plaque area and cIMT. Carotid plaque area was greater in men with worse cardiovascular health score. No association was detected in women.